Online Shopping Experience Drives of Online Shopping Intention: Role of Omnichannel Shopping Trust - Marinao-Artiga, Enrique; Wei-Chen, Shih; Limongi, Ricardo; Laroze, Denise (Review of Business Management, 2025)
Purpose – This study proposes a model in which online shopping intention is a consequence of the online shopping experience in an omnichannel environment. Theoretical framework – The experience is formed through the interaction between a consumer's cognitive and emotional experiences, with omnichannel shopping trust playing a crucial mediating role in the relationship between online shopping experience and shopping intention. The theoretical model is based on the Stimulus-Organism-Response (S-O-R) framework. Design/methodology/approach – Data analysis was performed using structural equation model analysis. Systematic random probability sampling was used to recruit 600 consumers, all with experience with omnichannel shopping in Chilean retail settings. Findings – Online shopping intention results from the interaction between cognitive and emotional experiences. Omnichannel shopping trust partially mediates the online shopping experience's effect on shopping intentions. Research Practical & Social implications – This study has important implications for digital platform managers and retailers who want to deliver an optimal omnichannel experience. Originality/value – In an omnichannel environment, the retailer needs to establish a close link through the cognitive and emotional experience of the shopper.